Does doing good pay off? The impact of corporate social responsibility (CSR) on firm performance: Evidence from Chinese listed companies - SHI, Huizhi (2022)
Although an increasing number of Chinese companies are recognizing the importance of corporate social responsibility (CSR), the majority of them are still not fully implementing CSR initiatives at present. The purpose of this study is to investigate the impact of CSR on firm accounting and market-based performance in China. Drawing upon stakeholder, legitimacy, resource dependence, and institutional theories, this empirical study employs Ordinary Least Squares (OLS) regression analysis to test a dataset for 2,735 firm-year observations from Chinese listed companies between 2010 and 2016. The results show that CSR has a significant positive influence on both corporate financial and market-based performance, and that this positive impact is strengthened by the advertising intensity and the level of the companies’ own profitability. The results also suggest that manufacturing companies are likely to financially benefit more from CSR than those in other industries. These findings provide theoretical and practical implications, indicating that companies should be more actively involved in CSR activities for their performance improvement.